Peripheral Nerve Regeneration Is Independent From Schwann Cell p75NTR Expression - Gonçalves, Nádia P.; Mohseni, Simin; El Soury, Marwa; Ulrichsen, Maj; Richner, Mette; Xiao, Junhua; Wood, Rhiannon J.; Andersen, Olav M.; Coulson, Elizabeth J.; Raimondo, Stefania; Murray, Simon S.; Vægter, Christian B. (Frontiers in Cellular Neuroscience, 2019)
Schwann cell reprogramming and differentiation are crucial prerequisites for neuronal regeneration and re-myelination to occur following injury to peripheral nerves. The neurotrophin receptor p75NTR has been identified as a positive modulator for Schwann cell myelination during development and implicated in promoting nerve regeneration after injury. However, most studies base this conclusion on results obtained from complete p75NTR knockout mouse models and cannot dissect the specific role of p75NTR expressed by Schwann cells. In this present study, a conditional knockout model selectively deleting p75NTR expression in Schwann cells was generated, where p75NTR expression is replaced with that of an mCherry reporter. Silencing of Schwann cell p75NTR expression was confirmed in the sciatic nerve in vivo and in vitro, without altering axonal expression of p75NTR. No difference in sciatic nerve myelination during development or following sciatic nerve crush injury was observed, as determined by quantification of both myelinated and unmyelinated nerve fiber densities, myelinated axonal diameter and myelin thickness. However, the absence of Schwann cell p75NTR reduced motor nerve conduction velocity after crush injury. Our data indicate that the absence of Schwann cell p75NTR expression in vivo is not critical for axonal regrowth or remyelination following sciatic nerve crush injury, but does play a key role in functional recovery. Overall, this represents the first step in redefining the role of p75NTR in the peripheral nervous system, suggesting that the Schwann cell-axon unit functions as a syncytium, with the previous published involvement of p75NTR in remyelination most likely depending on axonal/neuronal p75NTR and/or mutual glial-axonal interactions.